1990
DOI: 10.1007/bf00174018
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase isozyme expression in prenatal rat heart

Abstract: The distribution pattern of creatine kinase (E.C 2.7.3.2) isozymes in prenatal rat heart and skeletal muscle was studied by immunohistochemistry. Between embryonic day (ED) 12-18, creatine kinase M (CK-M) is heterogeneously expressed in the heart: a pronounced staining of CK-M is first observed in the outflow tract and the trabeculae of the right ventricle (ED12-14), and subsequently in the venous valves, the interatrial septum and the sinoatrial node. From ED18 onwards, a homogeneous expression of CK-M is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…During the late embryonic and early fetal stage, CK-M expression around the developing semilunar valves of aorta and pulmonary trunk is very high. A similar phenomenon is also observed in chicken (Lamers et al, 1989) and rat (Hasselbaink et al, 1990) embryos. In addition, a high expression of j3-MHC is observed in the myocardium of the OFT of the human heart (Wessels et al, 1990b).…”
Section: Ck In the Outflow Tract Of The Developing Heartsupporting
confidence: 82%
See 2 more Smart Citations
“…During the late embryonic and early fetal stage, CK-M expression around the developing semilunar valves of aorta and pulmonary trunk is very high. A similar phenomenon is also observed in chicken (Lamers et al, 1989) and rat (Hasselbaink et al, 1990) embryos. In addition, a high expression of j3-MHC is observed in the myocardium of the OFT of the human heart (Wessels et al, 1990b).…”
Section: Ck In the Outflow Tract Of The Developing Heartsupporting
confidence: 82%
“…several mammalian species during fetal life. For the developing rat heart it has been demonstrated that around the day 11 of development (i.e., Carnegie stage 12), the CK-B isoform is the first isoform to appear (Ziter, 1974;Hasselbaink et al, 1990). At day 12 of development (i.e., Carnegie stage 13) the presence of CK-M can be demonstrated.…”
Section: The Appearance Of Ck Lsoforms In the Developing Mammalian Hementioning
confidence: 99%
See 1 more Smart Citation
“…In earlier investigations on the development of atrioventricular specialized tissue in the human heart, Anderson and Taylor (1972) demonstrated that cholinesterase was expressed in the myocardium of the atrioventricular junction. Studies on other mammalian species have shown that the junctional areas between the different segments of the embryonic and fetal heart are also characterized by the expression of acetylcholinesterase (Lamers et al, 1987), by a low level of creatine kinase (Hasselbaink et al, 1990) and, in addition, by the expression of a neurofilament-like protein (Gorza et al, 1988, Gorza andVitadello, 1989) and the virtual absence of connexin-43, a main component of fast-conducting gap-junctions (Van Kempen et al, 1991). These observations suggest an important role for these areas in the regulation in the propagation of the cardiac impulse in early developmental stages.…”
mentioning
confidence: 99%
“…Muscle-specific creatine kinase (MCK) gene transcripts were found in the wall of only one ventricle in the mouse (Lyons 1994) and MCK isozyme was expressed first in the outflow tract and right ventricle in the rat (Hasselbaink et al 1990). In cardiac actin transgenes, expression was lower in the right ventricle than in the left ventricle (Biben et al 1996).…”
Section: Ca II Expression In the Left Ventricular Myocardiummentioning
confidence: 99%